Pandangan Akidah Muhammad Yusuf As-Sanusi dalam Kitab Ummul Barahin - Fuady, Farkhan Fuady (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
This paper aims to examine the views of the aqidah of Muhammad Yusuf As-Sanusi in the Book of Ummul Barahin. He is an important scholar in the science of faith. Various works, especially in the science of faith are still studied today. One of his works in the field of faith is the Book of Ummul Barahin. The book that discusses the science of faith and has four important points in it. The four are the law of reason, the characteristics of Allah SWT, the characteristics of the messenger of Allah SWT and the views regarding the two sentences of creed. The figure of Yusuf As-Sanusi has an important role in the development of faith. The concept developed by Yusuf As-Sanusi regarding the concept of aqidah is to understand the important points in the Ummul Barahin Book..